(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Accidental fall cases which lead to sudden death are common among medicolegal post-mortem in all institutes, unexpectedly in some cases during autopsy rare underlying cardiac or brain pathologies are revealed. History of incident and injuries in those cases are not enough to conclude cause of death, pre-existing disease could precipitate death during incident. In this case, deceased was slipped while washing his hands and sustained minor external injuries. Autopsy revealed large membranous Ventricular Septal Defect (VSD), dilated right ventricle and pulmonary artery, pulmonary edema and cerebral edema. Although patient was a diagnosed case of left to right shunt and Eisenmenger Syndrome (ES), he was perfectly stable under specialist treatment. This rare case revealed gross findings of Eisenmenger syndrome due to ventricular septal defect, in the ground of sudden physical trauma sustained due to accidental fall as a potential bothersome factor to underlying natural disease process leading to death.